INVERSE PROBLEM FOR DIFFERENTIAL OPERATORS WITH BOUNDARY CONDITIONS DEPENDENT ON EIGENPARAMETER - HASAN, SHARMEEN IZAT (Fırat Üniveristesi, 2020)
Bu tezde, spektral parametre içeren sınır kosullu ikinci dereceden diferansiyel denklem için potansiyel fonksiyon q için bir formülü veriyoruz. Bunun için öncelikle çalısmada kullanacagımız bazı temel bilgileri tanım ve teorem olarak sunduk. Üçüncü kısımda, Dirichlet sartlı problem için ters nodal problemin çözümü verilmis ve buradaki sonuçların ispatına gerek duyulmamıstır. Sonra, özdegerlerin, nodal noktaların ve nodal uzunlukların asimptotik ifadesini elde ettik. Tüm bunlardan sonra, q potansiyel fonksiyonunu elde etmek kolaydır. Metod olarak, diger yöntemlerden farklı bir avantaja sahip olan Prüfer dönüsümünü kullandık. Çünkü bu yöntemde herhangi bir özfonksiyon bilgisine ihtiyacımız yoktur. Anahtar Kelimeler: Sturm-Liouville,ters problemler, özdegerler, Prüfer dönüsümü, nodal nokta.

In this thesis, we give a reconstruction formula for the potential q for a second order differential equation with boundary condition which contains spectral parameter. For this, we give some definitions and theorems about regular case. In the third part, we give some results for inverse nodal problem with Dirichlet conditions. In this part, all theorems are given without proofs. Then, we obtain asymptotic express of eigenvalues, nodal points and nodal lengths. after all of these, it is not difficult to obtain the potential function q. As methodology, we use Prüfer substitution that has an advantage different from other methods. Because in this method, we do not need any information of eigenfunctions. Keywords: Sturm-Liouville, Inverse Problems, Eigenvalues, Prüfer substitutions, Nodal points.
Özparametreye bağlı diferensiyel operatörler için ters problem
Keywords: Matematik